The Pedigree of a Syrian Bronze in the Walters Art Gallery, Baltimore, and some Stylistic Crosscurrents in the Late Third Millennium B.C. - Vorys Canby, Jeanny
1967-68, publ 1969; Walters Art Gallery 54.788.